Comparative Immunogenicities of Full-Length Plasmodium falciparum Merozoite Surface Protein 3 and a 24-Kilodalton N-Terminal Fragment - Imam, Maryam (American Society for Microbiology, 2011)
Recombinant Plasmodium falciparum merozoite surface protein 3 (PfMSP3F) and a 24-kDa fragment from its N terminus (MSP3N) that includes the essential conserved domain, which elicits the maximum antibody (Ab)-dependent cellular inhibition (ADCI), were expressed as soluble proteins in Escherichia coli. Both proteins were found to be stable in both soluble and lyophilized forms. Immunization with MSP3F and MSP3N formulated separately with two human-compatible adjuvants, aluminum hydroxide (Alhydrogel) and Montanide ISA 720, produced significant antibody responses in mice and rabbits. Polyclonal Abs against both antigens recognized native MSP3 in the parasite lysate. These two Abs also recognized two synthetic peptides, previously characterized to possess B cell epitopes from the N-terminal region. Antibody depletion assay showed that most of the IgG response is directed toward the N-terminal region of the full protein. Anti-MSP3F and anti-MSP3N rabbit antibodies did not inhibit merozoite invasion or intraerythrocytic development but significantly reduced parasitemia in the presence of human monocytes. The ADCI demonstrated by anti-MSP3N antibodies was comparable to that exhibited by anti-MSP3F antibodies (both generated in rabbit). These results suggest that the N-terminal fragment of MSP3 can be considered a vaccine candidate that can form part of a multigenic vaccine against malaria.